(Re)rethinking the representation of indigenous peoples in North America - Crhák, Ondřej (Dějiny – teorie – kritika, 2025)
This paper explores the representation and re-evaluation of Native Americans in the context of U.S. and Czech societies, focusing on shifts from colonial narratives to contemporary postcolonial discourse. It examines recent developments, such as President Joe Biden’s apology to Indigenous communities and the handling of Native American cultural representations in Czech public events, like the General Custer Memorial in Prague. The study highlights the persistence of romanticized views in Czech culture, contrasting them with the critical self-reflection emerging in American institutions. By analyzing museum exhibits and public perceptions, the paper aims to reveal differences in the portrayal and understanding of Indigenous cultures in the Czech Republic and the United States, questioning the cultural and historical factors underlying these diverging approaches.